PENGARUH KECERDASAN EMOSIONAL DAN DUKUNGAN ORANG TUA TERHADAP MOTIVASI BELAJAR SERTA IMPLIKASINYA TERHADAP HASIL BELAJAR - Rizky Surya Pratama; Ai Nur Solihat; Gugum Gumilar (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of emotional intelligence and parental support on learning motivation and its implications for learning outcomes in class X economics subjects at SMA Negeri 8 Tasikmalaya. This study uses a survey research method with a quantitative approach, the sampling technique uses probability sampling by means of simple random sampling with a total of 208 people. The results of research using Path Analysis show that there is a significant influence between emotional intelligence on learning motivation, there is a significant influence between parental support on learning motivation, there is a significant influence between emotional intelligence on learning outcomes, there is a significant influence between parental support on learning outcomes, there is a significant influence between learning motivation on learning outcomes, there is a significant influence between emotional intelligence on learning outcomes through learning motivation and there is a significant influence between parental support on learning outcomes through learning motivation.